A Performance-Centred Competency-Based Approach to Quality University Teaching - Magda Francisca Cejas Martínez; Derling Jose Mendoza Velazco; Mercedes Navarro Cejas; José Lenin Rogel Villacis; Yanet Marisol Ortega Freire (National Research Mordova State University, 2019)
Introduction. In order to encourage more flexible working environments and establish generators of sustainable development for participating countries through an educated society, various international organisations that intervene in the quality dimension within the framework of a systemic approach to Higher Education, including the World Bank, have made multiple efforts to establish various recognitions, certifications and credits pertaining to competency-based education. Materials and Methods. The research, featuring a study of theoretical-interpretative design, was based around the qualitative paradigm. Information was obtained by means of semi-structured interviews with 14 lecturers from different universities in the city of Quito in Ecuador. The data obtained were triangulated with a review of the literature carried out by the researchers. Results. The informants considered cognitive competencies to be the most relevant within the context of teacher formation. Research, planning and organisation skills were not established in importance due to university professionalisation. Additionally, the need to establish curricular changes in the Ecuadorian university pedagogy was confirmed. Discussion and Conclusion. After contrasting the opinions of university professors and formation theories, a theoretical reflection is presented in which the importance of unifying professional formation and investigative competencies is emphasised. This unification allows the quality of higher education centred around the teacher as the main actor to be increased.